Composite girder to fulfill the needs of 60 up to 80 m span bridge for toll road projects in Indonesia - Trisaputra Zuna Herry; Budi Astuti Zulaikha (MATEC Web of Conferences, 2019)
Ministry of Public Works and Housing of Indonesia is targeting to complete the construction of 1.000 km of new toll road projects by the end of 2019. In 2015 until August 2018, 443 km new toll roads have been operated and 1.400 km are under construction. Various types of structure for elevated toll road constructions are applied to meet the geometry and safety requirements such as cast in-situ balanced cantilever, steel I-girder, and steel box are becoming type of elevated toll construction to be applied. To meet the requirements of construction methods, construction time completion, and material volume efficiency, Indonesia Toll Road Authority on behalf Ministry of Public Works and Housing gives opportunities to toll road investors to apply the new technology as the proper selection. Composite Girder technology named Sbarch is proposed for Krian Legundi Bunder Manyar toll road project to cross at SUMO Junction. Compares Sbarch among cast in situ balanced cantilever, steel I-girder and steel box, Sbarch can comply for all requirement that cannot be fulfilled by others method such as with finish grade requirement, to road geometry alignment, accessibility, workability, and steel tonnage reducing.